Association between stigma towards HIV and MSM and intimate partner violence among newly HIV-diagnosed Chinese men who have sex with men - Na Wang; Bo Huang; Yuhua Ruan; K. Rivet Amico; Sten H. Vermund; Shimin Zheng; Han-Zhu Qian (BMC, 2020)
Abstract Background HIV- and MSM-related stigma are well documented as common for Chinese men who have sex with men (MSM) living with HIV, yet there is sparse literature on intimate partner violence (IPV) and its relationship with stigma in this vulnerable population. To evaluate the association between HIV-stigma and stigma related to homosexuality and IPV among newly HIV-diagnosed MSM in China. Methods Data were collected in the baseline survey among newly HIV-diagnosed Chinese MSM in a randomized clinical trial via face-to-face interviews. Univariate logistic and multivariate logistic regression analyses were performed to assess the associations between IPV and HIV- and MSM-related stigma. Results Of 367 newly HIV-diagnosed Chinese MSM, 23.7% experienced any IPV, including 16.6% physical, 7.4% psychological and 5.2% sexual IPV. Positive associations were found between HIV- and MSM-related stigma and IPV. Men with high HIV-related stigma (score ≥ 27) were 1.67 times as likely to experience any IPV as those with low stigma (adjusted odds ratio [AOR]: 1.67, 95% confidence interval [CI]: 1.02-2.76). Men with high MSM-related stigma (score ≥ 6) were 1.99 times as likely to experience any IPV as those with low stigma (AOR: 1.99, 95% CI: 1.18-3.36). Conclusions HIV- and MSM-related stigmas was positively associated with IPV experiences among newly diagnosed MSM in China. The manner in which stigma may exacerbate IPV, and/or the influence of IPV on worsening stigma should be further evaluated. The high prevalence of IPV and stigma in this population suggests that interventions should be taken to reduce stigma and prevent this risky behavior among MSM.